Air-cathode interface-engineered electrocatalyst for solid-state rechargeable zinc-air batteries - Manna, Narugopal; Singh, Santosh K.; Kurian, Maria; Torris, Arun; Kurungot, Sreekumar (ACS Applied Energy Materials, 2022)
Solid-state rechargeable zinc-air batteries (ZABs) are gaining interest as a class of portable clean energy technology due to their advantages such as high theoretical energy density, intrinsic safety, and low cost. It is expected that an appropriately triple-phase boundary (TPB) engineered, bifunctional oxygen reaction (OER and ORR) electrocatalyst at the air- electrode of ZABs can redefine the performance characteristics of these systems. To explore this possibility, an electrode material consisting of manganese- cobalt-based bimetallic spinel oxide (MnCo2O4)-supported nitrogen-doped entangled graphene (MnCo2O4/NEGF) with multiple active sites responsible for facilitating both OER and ORR has been prepared. The porous 3D graphitic support significantly affects the bifunctional oxygen reaction kinetics and helps the system display a remarkable catalytic performance. The air electrode consisting of the MnCo2O4/NEGF catalyst coated over the gas diffusion layer (GDL) ensures the effective TPB, and this feature works in favor of the rechargeable ZAB system under the charging and discharging modes. As an important structural and functional attribute of the electrocatalyst, the porosity and nitrogen doping in the 3D conducting support play a decisive aspect in controlling the surface wettability (hydrophilicity/hydrophobicity) of the air electrode. The fabricated solid-state rechargeable ZAB device with the developed electrode displayed a maximum peak power density of 202 mW cm(-2), which is significantly improved as compared to the one based on the Pt/C + RuO2 standard catalyst pair (124 mW cm(-2)). The solid-state device which displayed an initial charge-discharge voltage gap of only 0.7 V at 10 mA cm(-2) showed only a small increment of 86 mV after 50 h.
Keywords: air-cathode interface; bifunctional oxygen catalyst; N-doped entangled graphene; solid-state zinc-air battery; spinel oxides

Advanced 3D network of N-doped graphitic carbon with FeNi alloy embedding for high-performance rechargeable Zn-air batteries - Pandikassala, Ajmal; Kurian, Maria; Gangadharan, Pranav K.; Torris, Arun; Kurungot, Sreekumar (Advanced Sustainable Systems, 2024)
Despite the significant progress in Zn-air batteries (ZABs), their widespread use in the rechargeable sector is hindered due to the scarcity of efficient bifunctional oxygen catalysts that can catalyze both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). To address this, an ORR/OER bifunctional electrocatalyst is designed with ultrafine alloyed FeNi nanoparticles encapsulated in a 3D interconnected N- doped carbon network structure, featuring a carbon nitride backbone enclosed in graphitic carbon. The FeNi electrocatalyst (3DFeNiPDC) showed good bifunctional activity toward both ORR and OER in the basic medium with a low overpotential value of 30 mV for ORR and 6 mV for OER compared to its state-of-the-art counterparts Pt/C, and RuO2, respectively. Utilizing 3DFeNiPDC in a rechargeable Zn-air battery (RZAB) yields an open circuit voltage (OCV) of 1.35 V, a maximum power density of 232 mW cm-2, and an energy density of 707 W h kg-1. Additionally, a flexible RZAB employing 3DFeNiPDC demonstrates an OCV of 1.4 V with various bending angles. These finding suggest 3DFeNiPDC as a viable alternative to noble metal-based RZABs, offering superior bifunctional electrocatalytic activity and stability, particularly with its enhanced air-breathing properties facilitating improved operability under practical conditions. The bifunctional electrocatalytic activity of FeNi alloy nanoparticles embedded in a 3D- interconnected N-doped graphitic carbon (3DFeNiPDC) for both oxygen reduction and oxygen evolution is studied. The 3D architecture and core-shell characteristics of FeNi alloy nanoparticles provide better activity and stability for oxygen electrocatalysis. The electrocatalytic activity of 3DFeNiPDC has been exploited for liquid-state and solid-state flexible rechargeable zinc-air batteries. image
Keywords: Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable flexible zinc-air battery

Advances in polymer electrolyte design strategies for highly efficient supercapacitors and Zn-based batteries - Puthiyaveetil, Priyanka Pandinhare; Babu, Athira; Kurian, Maria; Kurungot, Sreekumar (Chemical Communications, 2025)
Electrolytes play a crucial role in the performance of electrochemical energy storage systems, such as batteries and supercapacitors. Their main function is to act as a medium for ion transport between the electrodes, which is essential for the charge and discharge processes. Beyond this, the electrochemical performance of the device is strongly affected by the various properties of the electrolytes such as their ionic conductivity, chemical, thermal and electrochemical stability, chemical compatibility, etc. The intrinsic limitations of the aqueous electrolytes such as their decomposition during high voltage operations has led to the development of better electrolytes for batteries and supercapacitors. These included non-aqueous electrolytes, inorganic solid-state electrolytes, and gel polymer electrolytes. This feature article reviews the various approaches to designing a highly efficient polymer electrolyte for the targeted application along with the suitable device fabrication strategy adopted in the current literature to achieve a balanced electrochemical performance compared with a liquid electrolyte-based device.